A framework for exploring the macroeconomic determinants of systematic risk - Torben G. Andersen; Tim Bollerslev; Francis X. Diebold; Jin Wu (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
We selectively survey, unify and extend the literature on realized volatility of financial asset returns. Rather than focusing exclusively on characterizing the properties of realized volatility, we progress by examining economically interesting functions of realized volatility, namely realized betas for equity portfolios, relating them both to their underlying realized variance and covariance parts and to underlying macroeconomic fundamentals.
urn:nbn:de:hebis:30-10803
Keywords: G12; 330; Realized volatility; realized beta; conditional CAPM; business cycle